Implikasi Hukum Terhadap Salah Ukur Tanah Milik Masyarakat oleh BPN Kota Langsa - Wahyu Ramadhani (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
This research seeks to examine the legal implications of the mis-measurement of community-owned land by the National Land Agency (BPN) and what are the efforts and obstacles of BPN in resolving the mis-measurement. This type of research was a normative and empirical juridical research. The data used in this study was primary data carried out by examining various documents in reviewing the problem. In addition, this study also used secondary data obtained through interviews with research respondents and direct observations. The data obtained is then analyzed descriptively and qualitatively. The results of the study indicate that the law of mis-measurement by BPN can be sued and canceled due to errors in land measurement, especially which can have an effect on land owners in carrying out a deed of sale and purchase, therefore the consequences of this law can be said to be administrative defects. The obstacle in resolving the mis-measurement is the lack of human resources from the BPN who understands the resolution of land disputes through mediation due to the lack of mediators.